Intestinal Mucosal Barrier Is Injured by BMP2/4 via Activation of NF-κB Signals after Ischemic Reperfusion - Kang Chen; Wei Xie; Binyu Luo; Weidong Xiao; Daniel H. Teitelbaum; Hua Yang; Kebin Zhang; Chaojun Zhang (Mediators of Inflammation)
Intestinal ischemic reperfusion (I/R) can cause dysfunction of the intestinal mucosal barrier; however, the mechanism of the intestinal mucosal barrier dysfunction caused by I/R remains unclear. In this study, using intestinal epithelial cells under anaerobic cultivation and an in vivo rat intestinal I/R model, we found that hypoxia and I/R increased the expression of BMP2/4 and upregulated BMP type Ia receptor and BMP type II receptor expression. We also found that exogenous BMP2/4 can activate the ERK and AKT signaling pathways in rat small intestine (IEC-6) cells, thereby activating NF-κB signaling, which leads to increased levels of inflammatory factors, such as TNF-α and IL-6. Furthermore, recombinant BMP2/4 decreased the expression of the tight junction protein occludin via the activation of the NF-κB pathway; these effects were abolished by treatment with the BMP-specific antagonist noggin or the NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC). All these factors can destroy the intestinal mucosal barrier, thereby leading to weaker barrier function. On the basis of these data, we conclude that BMP2/4 may act as the pathogenic basis for intestinal mucosal barrier dysfunction when the intestines suffer an I/R injury. Our results provide background for the development pharmacologic interventions in the management of I/R injury.